PESANTREN: LUMBUNG PENGUATAN NASIONALISME BAGI SANTRI - Hairul Puadi (Pascasarjana Institut Agama Islam (IAI) Al-Qolam, 2023)
Looking at the typology of pesantren, curriculum structure and direction of pesantren education, the model for strengthening nationalism is built through three stages, namely: First, input gain. This stage consists of at least three stages, namely: Stage one, scientific transmission which is carried out in three ways: (a) Teaching selected yellow books. (b) Ijab qabul guardian of students. (c) The concept of “barakah”. Stage two, transmission of activity. This stage is implemented in certain activity events. Stage three, religious transmission, such as worship (ubudiyyah), transactional practices (mu'amalah), politics (siyasa). Second, strengthening the process of nationalism in Islamic boarding schools. The strengthening process is in the form of grounding the values of tolerance (at-tasammuh), the values of balance (at-tawazun), and the values of moderation (tawasuth). This is reflected in the contents of the curriculum being taught, such as the yellow book. Debate over issues with nuances of difference (khilafiyah) with a variety of reasons makes the students understand more that differences are real. Third, strengthening the output of nationalism in Islamic boarding schools is at least a strengthening model by maintaining and overseeing Islamic boarding school graduates through communication and interaction with the kyai and their alma mater. So that pesantren graduates become alumni and individuals who are Islamic, humane, tolerant, civilized, and loving. Keywords: Pesantren, Nationalism, Strengthening Input, Process, Output